THE ROLE OF THE HEAD OF SCHOOL AS SUPERVISOR IN DEVELOPING TEACHERS' PEDAGOGIC COMPETENCE TO ACHIEVE QUALITY OF GRADUATES IN MI NURUL ISLAM, BEKASI CITY - Maryati; Yayat Suharyat; Nana Danapriatna (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2021)
This research is specifically to find out how the role of the principal as a supervisor in developing the pedagogical competence of teachers to achieve the quality of graduates at MI Nurul Islam Bekasi. This study uses a qualitative or naturalistic descriptive approach. Data collection using participant observation techniques, interviews, questionnaires and documentation. Checking the validity of the data using three techniques, namely persistence of observation, triangulation and member checking. Meanwhile, for data analysis using three flow of activities, namely data reduction, data presentation and conclusion drawing/verification. PKS (Assistant Principal). Second, the principal has not played a good role as a supervisor. Third, the implementation of supervision has not been able to run well because there are several inhibiting factors, one of which is the teacher lacks confidence in the supervisor's ability, so there is no motivation to welcome supervision activities. Fourth, teachers expect continuous supervision carried out by professional supervisors who can guide and foster teachers in developing pedagogical competencies and teaching abilities to create good quality graduates.